OCD and autism : a clinician's guide to adapting CBT - Russell, Ailsa; Jassi, Amita; Johnston, Kate, 1979- (Jessica Kingsley Publishers, 2019)
This step-by-step manual explains how to adapt CBT (Cognitive Behaviour Therapy) approaches to OCD (Obsessive Compulsive Disorder) for autistic children and adults. It outlines why there is the need to adapt treatment for the autistic population, and includes detailed guidance on each phase of the approach. It explains assessment of OCD in autism, the links between the two conditions and difficulties in identifying aspects of OCD in autistic people. The book offers advice on dealing with difficult issues and on the next steps after treatment is complete. Accompanying worksheets and handouts are available to download.